Lymphocytes - Salih Istifli, Erman; Basri İla, Hasan (IntechOpen, 2019)
Although all the features of the immune system have not been fully resolved yet, the knowledge we have gained from studies on lymphocytes, the basic elements of the immune system, is quite lucid. For this reason, the significance of lymphocytes (the cells that are the source of most of the information we have obtained about the human genome, the negative effects of drugs on the genetic system, the development and behavior of immune system, antigen-antibody association, cytotoxic adaptive immunity, antibody-driven adaptive immunity, cancer and autoimmune diseases) is clear. Studies on lymphocytes will not only help us develop tools to combat human diseases more effectively in the future, but will also help us understand how evolution shapes the immune system in living organisms.